2019
DOI: 10.1364/oe.27.009343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ray position sampling on the visual responses of 3D light field displays

Abstract: A 3D light field display typically reconstructs a 3D scene by sampling either the projections of the 3D scene at different depths or the directions of the light rays apparently emitted by the 3D scene and viewed from different eye positions. These light field display methods are potentially capable of rendering correct or nearly correct focus cues and therefore addressing the well-known vergence-accommodation conflict problem plaguing the conventional stereoscopic displays. However, very limited efforts have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 27 publications
(52 reference statements)
1
32
0
Order By: Relevance
“…If a certain accommodation shift exists with respect to the RDP, there will be residual VAC that may still cause visual discomfort. In fact, a few studies [10,11,13] have suggested certain accommodation shifts in real-image MLA-based LFDs when the sampled ray number of a reconstructed image point is not sufficient, e.g., less than 4-by-4 rays sampled [10,11]. However, it has been little examined whether the accommodation shift still exists when the sampled ray number is sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…If a certain accommodation shift exists with respect to the RDP, there will be residual VAC that may still cause visual discomfort. In fact, a few studies [10,11,13] have suggested certain accommodation shifts in real-image MLA-based LFDs when the sampled ray number of a reconstructed image point is not sufficient, e.g., less than 4-by-4 rays sampled [10,11]. However, it has been little examined whether the accommodation shift still exists when the sampled ray number is sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested in our previous works [24,27], by referring to the two reference planes described above, the 4-D light field function, L (s, t, u, v), physically sampled by the pixels on the microdisplay and the lenslets of the MLA in the object space of an InI-HMD, can be conveniently mapped to the light field function L'(x c , y c , x v , y v ) defined in the virtual image or visual space, as if the ray bundles of the elemental views are emitted by pixels located on the virtual CDP toward the viewing window. Figure 2(a) illustrate the simplified process of light field rendering in the visual space, where the ray positions of the light field function are sampled by the projected virtual pixels (x c , y c ) on the virtual CDP and the ray directions are defined by the projected coordinates (x v , y v ) of the array elements on the viewing window.…”
Section: (B)mentioning
confidence: 59%
“…However, due to the unique property of an InI-HMD, the ray directions of the light fields play a very important role in designing such a display system. As discussed above, incorrect sampling of ray directions will not only affect the integration of the elemental images but also potentially lead to uneven number of elemental views for reconstructed light field targets and thus misrepresented focus cues [24,27]. In the case of severe pupil aberration, it is even possible that the number of elemental views encircled by a viewer's eye pupil reduces to be less than two so that it makes no difference from a conventional stereoscopic display system and fail to properly render true light fields.…”
Section: Optimizing Ray Directional Sampling Of Light Fieldmentioning
confidence: 99%
“…In this technique, the virtual image is displayed in front of the human eye through an optical system and AR eyepiece and ambient light from a real object can pass incident on the human eye through the AR eyepiece without distortion. The combination of holography and VR or AR display to achieve a true 3D display is quite intuitive and thus desirable, which can avoid the accommodation convergence conflict problem existing in binocular parallax-based 3D displays [12,13].…”
Section: Introductionmentioning
confidence: 99%